ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL MATERI ARITMATIKA SOSIAL PADA PEMBELAJARAN DARING - Lusi Amalia; Gida Kadarisma (IKIP Siliwangi, 2022)
During the Covid-19 pandemic, learning is carried out online, this does not become an obstacle for learning mathematics, especially on the subject of social arithmetic which is closely related to daily activities. The purpose of this study is to analyze and explain students' mistakes when working on social arithmetic problems online. The research method uses descriptive qualitative. Data collection techniques by distributing 5 items of description. The subjects in the study were seventh grade students of Dharma Kartini Middle School, Cimahi. The research stages include data reduction, data delivery and data inference. The results of this study show an error in indicator one determining the relationship between selling and buying prices and indicator two determining the relationship between profit and loss in the low category, indicators of the relationship between net, gross and tare and indicators solving problems related to social arithmetic in the medium category and indicators solving problems with respect to discounts in the high category. The underlying factors are the lack of accuracy of students in pronouncing the questions, lack of understanding of concepts and students still not understanding arithmetic operations.